2012
DOI: 10.1186/1744-8603-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Cancer registries in four provinces in Turkey: A case study

Abstract: BackgroundThe burden of cancer affects all countries; while high-income countries have the capacity and resources to establish comprehensive cancer control programs, low and middle-income countries have limited resources to develop such programs. This paper examines factors associated with the development of cancer registries in four provinces in Turkey. It looks at the progress made by these registries, the challenges they faced, and the lessons learned. Other countries with similar resources can benefit from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…[2] Breast cancer is the second most common cancer overall (1.7 million cases, 11.9%) but is the fifth most common cause of death (522,000, 6.4%) because of its relatively favorable prognosis; these were followed, in terms of incidence, by colorectal cancer (1.4 million cases, 694,000 deaths), prostate cancer (1.1 million cases, 307,000 deaths), stomach cancer (951,000 cases, 723,000 deaths), and liver cancer (782,000 cases and 745,000 deaths). [4] The first five most common cancer types in Turkey are similar to those in the world and other developed countries. [5] In our study, the first five most common cancers were skin (n=374, 17.0%), lung (n=205, 9.3%), colorectal (n=204, 9.3%), breast (n=192, 8.7%), and prostate (n=174, 7.9%), respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2] Breast cancer is the second most common cancer overall (1.7 million cases, 11.9%) but is the fifth most common cause of death (522,000, 6.4%) because of its relatively favorable prognosis; these were followed, in terms of incidence, by colorectal cancer (1.4 million cases, 694,000 deaths), prostate cancer (1.1 million cases, 307,000 deaths), stomach cancer (951,000 cases, 723,000 deaths), and liver cancer (782,000 cases and 745,000 deaths). [4] The first five most common cancer types in Turkey are similar to those in the world and other developed countries. [5] In our study, the first five most common cancers were skin (n=374, 17.0%), lung (n=205, 9.3%), colorectal (n=204, 9.3%), breast (n=192, 8.7%), and prostate (n=174, 7.9%), respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[4] However, it has been acknowledged that there is a "significant lack of relevant cancer data from developing countries. " Registries require time, effort, expertise, and skills development so that they can become functional and meet international standards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, some pilot studies have been published about age-specific incidence ratios of cancers, such as breast, melanoma, and colorectal cancers. All these studies have shown an increasing trend (Eser et al, 2010a;Eser and Özdemir, 2012;Stillman et al, 2012). Turkey has a growing economy, but with the increasing of the aged population over 65 years, some socioeconomic and health problems are seen.…”
Section: Epidemiology Of Cancer In Turkeymentioning
confidence: 99%